Upper limb kinetics between two different stances in a tennis forehand drive: a preliminary study - Pedro, B.; Cabral, S.; Veloso, A. P. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to compare the joint moments of force of the upper limb between one forehand drive performed in quasi-static stance (QSS) (with both feet on the ground at the impact) and one forehand performed with a dynamic frontal weight transfer stance (DS) (with both feet off the ground at the impact). One high-performance tennis player was recorded with an optical system with a frequency of 240Hz during both techniques. Three forehands in QSS and three in DS were selected for analysis. Results demonstrated that the forehand performed with QSS could present higher moments of force, especially in the shoulder joint abdu/addu (QSS:45.5 vs DS:52.8 Nm), moreover, the DS presented higher racket velocity compared with the QSS forehand drive (DS: 32.7(0.4) vs QSS:31.5(0.4) m/s). The results of this study could present an important information for tennis coaches as for their players in order to understand which forehand technique creates higher joint loads, and, therefore adapt the practice for each situation.